1987
DOI: 10.1159/000177276
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Status in a Saudi Population – A Study in Riyadh

Abstract: Riboflavin is essential for several metabolic processes taking place in the human body. A deficiency of riboflavin has been reported to occur at a high prevalence in several populations, particularly in children and adolescents from low-socioeconomic groups. We investigated the riboflavin status in 502 Saudi males and 213 Saudi females using a determination of red-cell glutathione reductase activity in the presence and absence of flavin adenine dinucleotide. The population was grouped according to age and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…Our value for the prevalence of vitamin B 2 deficiency in southern Spain (see p. 663) was similar to that reported for a population of independently living elderly Spanish individuals (López-Sobaler et al 2002), and lower than that found for an elderly British population (Bailey et al 1997), elderly Guatemalan individuals (Boisvert et al 1993) and a Saudi population (El-Hazmi & Warsy, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…Our value for the prevalence of vitamin B 2 deficiency in southern Spain (see p. 663) was similar to that reported for a population of independently living elderly Spanish individuals (López-Sobaler et al 2002), and lower than that found for an elderly British population (Bailey et al 1997), elderly Guatemalan individuals (Boisvert et al 1993) and a Saudi population (El-Hazmi & Warsy, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…Riboflavin plays critical roles in maintaining energy supply and mucous membranes, producing hormones, and aiding fetal development. When deficient, it can cause oral inflammation, dermal dryness, stomatitis, and growth retardation [ 16 , 26 ]. Riboflavin is relatively stable to heat and oxidation but is easily destructive under alkaline conditions and ultraviolet (UV) and visible light exposure [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Riboflavin (vitamin B 2 ) is involved in growth promotion, oral mucosal protection, and in vivo oxidation and reduction. Riboflavin deficiency can cause stunted growth in children, stomatitis, glossitis, and angular stomatitis [14]. Niacin (vitamin B 3 ) governs the oxidation and reduction of nutrients, dilates peripheral blood vessels to promote blood circulation, and reduces cholesterol levels in the body.…”
Section: Introductionmentioning
confidence: 99%